Effect of day of the week on short‐ and long‐term mortality after emergency general surgery. Issue 7 (21st March 2017) - Gillies, M. A.; Lone, N. I.; Pearse, R. M.; Haddow, C.; Smyth, L.; Parks, R. W.; Walsh, T. S.; Harrison, E. M.
Abstract: Background: The effect of day of the week on outcome after surgery is the subject of debate. The aim was to determine whether day of the week of emergency general surgery alters short‐ and long‐term mortality. Methods: This was an observational study of all patients undergoing emergency general surgery in Scotland between 1 January 2005 and 31 December 2007, followed to 2012. Multilevel logistic and Cox proportional hazards regression were used to assess the effect of day of the week of surgery on outcome after adjustment for case mix and risk factors. The primary outcome was perioperative mortality; the secondary outcome was overall survival. Results: A total of 50 844 patients were identified, of whom 31 499 had an emergency procedure on Monday to Thursday and 19 345 on Friday to Sunday. Patients undergoing surgery at the weekend were younger (mean 45·9 versus 47·5 years; P < 0·001) and had fewer co‐morbidities, but underwent riskier and/or more complex procedures ( P < 0·001). Patients who had surgery at the weekend were more likely to have been operated on sooner than those who had weekday surgery (mean time from admission to operation 1·2 versus 1·6 days; P < 0·001). No difference in perioperative mortality (odds ratio 1·00, 95 per cent c.i. 0·89 to 1·13; P = 0·989) or overall survival (hazard ratio 1·01, 0·97 to 1·06; P = 0·583) was observed when surgery was performed at the weekend. There was no difference in overall survival after surgery undertaken on any particular day compared with Wednesday; a borderline reduction in perioperative mortality was seen on Tuesday. Conclusion: There was no difference in short‐ or long‐term mortality following emergency general surgery at the weekend, compared with mid‐week. Abstract : No weekend effect; Tuesday best?